2021
DOI: 10.3390/foods10123155
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Four Triterpenoids Isolated from Poriae Cutis

Abstract: In this study, triterpenoid compounds from Poriae Cutis were separated by high-speed countercurrent chromatography (HSCCC) and identified using ultra-high performance liquid chromatography quadrupole time-of-flight tandem mass spectrometry (UHPLC-QTOF-MS/MS) and nuclear magnetic resonance (NMR). The in vitro anti-inflammatory activities of the purified triterpenoids on RAW 264.7 cells were also investigated. Triterpenoids, poricoic acid B, poricoic acid A, dehydrotrametenolic acid, and dehydroeburicoic acid we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous study found that poricoic acid A could protect against acute kidney injury-to-chronic kidney disease transition in rats and attenuate fibroblast activation and abnormal extracellular matrix remodeling in renal fibrosis (Chen DQ et al, 2019;Chen DQ et al, 2020). Poricoic acid B could decrease the production of cytokines (TNF, IL-1B, and IL-6) (Zhang et al, 2021). And our data showed that poricoic acid C might interact with TNF and thus ameliorate renal injury of DKD.…”
Section: Discussionmentioning
confidence: 53%
“…Previous study found that poricoic acid A could protect against acute kidney injury-to-chronic kidney disease transition in rats and attenuate fibroblast activation and abnormal extracellular matrix remodeling in renal fibrosis (Chen DQ et al, 2019;Chen DQ et al, 2020). Poricoic acid B could decrease the production of cytokines (TNF, IL-1B, and IL-6) (Zhang et al, 2021). And our data showed that poricoic acid C might interact with TNF and thus ameliorate renal injury of DKD.…”
Section: Discussionmentioning
confidence: 53%
“…In this study, we identified poricoic acid B and polyporenic acid C as 6.7% and 28.1% of EPC, respectively. Pharmacological studies showed that porcine acid B has a strong anti-inflammatory effect ( Zhang et al, 2021 ). Polyporenic acid C potentiates insulin and induces differentiation of ST-13 preadipocytes ( Yang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…PAA appears to modulate multiple important signaling pathways, including NF-kB, PI3K/Akt (phosphatidylinositol-3-kinase/protein kinase B), and TGF-b, exerting anti-fibrotic effects in vivo and in vitro [10,11]. In addition, our laboratory study showed that PAB had higher anti-inflammatory activity than PAA by inhibiting NO production in RAW 264.7 cells induced by lipopolysaccharide (LPS) [12]. Studies have also found that PAA has an inhibitory effect on colon, kidney, prostate and breast cancer cells [13].…”
Section: X For Peer Review 2 Of 18mentioning
confidence: 79%
“…In our previous studies, it was shown that triterpenes promote the production of TNF-alpha, which plays a role in cell death and tumor progression [12]. It has been shown that tumor necrosis factor alpha can act directly on tumor cells and induce ROS within them, which is the rationale behind the use of cellular immunotherapy for targeted elimination of cancer cells [34].…”
Section: Effect Of Paa and Pab On Ros Production In Hepg2 Cellsmentioning
confidence: 99%